Analysis on Emotional Intelligence Among Telecom Employees (International Journal of Engineering and Computer Science, 2017)
The present research was carried out with the aim of assessing the Emotional Intelligence among employees of private and government telecom sector. The sample for the study comprised of 160 employed youths in telecom sector ( i.e 60 from BSNL and AIRTEL) of Jammu city. The sample was selected through multi stage sampling technique where the actual sample was selected randomly. The tool used for investigation was a standardized Emotional Intelligence scale developed by Chadha and Singh (2003). Results reveal that most of the sample youth had high to moderate level of emotional intelligence. There was a significant difference in level of emotional intelligence of employees among BSNL and AIRTEL, with more AIRTEL employees having higher levels of emotional intelligence than the employees of BSNL. Components wise analysis reveals that most of the sample youth had moderate level of emotional sensitivity and moderate to high level of emotional competency